Measuring fear evoked by the scariest animal: Czech versions of the Spider Questionnaire and Spider Phobia Beliefs Questionnaire - Polák, Jakub; Sedláčková, Kristýna; Janovcová, Markéta; Peléšková, Šárka; Flegr, Jaroslav; Vobrubová, Barbora; Frynta, Daniel; Landová, Eva (BMC psychiatry, 2022)
BACKGROUND: Although tiny in size and mostly harmless, spiders evoke exceptional fear in a significant part of the population and arachnophobia is one of the most common anxiety disorders with prevalence 2.7-6.1%. Two standard measures have been widely used to reliably assess the emotional and cognitive component of spider fear, the Spider Questionnaire (SPQ) and Spider Phobia Beliefs Questionnaire (SBQ). We aimed to develop and validate their Czech translations, describe distribution of spider fear in the Czech population, and analyse its association with disgust propensity and other sociodemographic characteristics. METHODS: In Phase 1, we developed Czech translations of both questionnaires using a back-translation procedure and then tested their psychometric properties against their English versions in a counterbalanced experimental design using the Mann-Whitney U test and two-sided t-test. In Phase 2, we analysed scores on the Czech SPQ and SBQ on a larger sample. We evaluated the effects of age, gender, level of education, biology background, and association with the assessments of snake fear (i.e. the Snake Questionnaire, SNAQ) and disgust propensity (i.e. the Disgust Scale-Revised, DS-R) using a Spearman correlation, redundancy analysis, and general linear models. RESULTS: We have demonstrated that the Czech SPQ and SBQ are equivalent to their originals and show excellent test-retest reliability (SPQ: 0.93; SBQ: 0.87-0.90). In total, 398 (10.3%) out of 3863 subjects reached the cut-off point for potential spider phobia. In addition, SPQ and SBQ scores were highly correlated (0.73-0.79), significantly more than with the SNAQ (0.21-0.32) or the DS-R (0.36-0.40). Two multivariate statistical methods revealed a significant association between the gender, age, level of education, biology background, or disgust propensity and the SPQ scores. CONCLUSION: The Czech SPQ and SBQ may produce reliable and valid assessments of spider fear, but they must be further psychometrically tested considering the limitation of this study before wider use. We corroborate previous findings that fear of spiders is significantly associated with sociodemographic variables, such as gender, age, or education, as well as with the individual level of disgust propensity.
Keywords: Reproducibility of Results; Česká republika; Czech Republic; Spiders; Animals; Phobic Disorders; lidé; fobie; Fear; strach; pavouci; Surveys and Questionnaires; Humans; zvířata; reprodukovatelnost výsledků; průzkumy a dotazníky